Performance Evaluation Of Programs And Activities In The Aspect Of Information And Communication Technology With A Logic Model Approach - Selvy Elida Haloho; Nanda Ayu Wijayanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study was conducted to evaluate the performance of programs and activities in the ICT aspect in order to determine the logical relationship between information and performance indicators that have been determined in the strategic planning documents of the Kutai Kartanegara Regency Government and Diskominfo, as well as the outcome sequence chart in accordance with the evaluation results in order to improve the performance of these programs and activities. This research is a qualitative study using a case study-based evaluation process. Primary data used is obtained from semi-structured interviews with respondents in the ICT and E-Governement Sectors. Analysis of program and activity performance data will use a logic model approach. The results showed that performance information already has a logical relationship, but its implementation cannot support the achievement of Diskominfo's KPI performance. Furthermore, there are still inconsistencies between the performance indicators that have been determined and those listed in the performance appraisal document. The recommended outcome sequence chart has been prepared in accordance with indicators related to the ICT aspect of SPBE. Diskominfo needs to reformulate information and performance indicators to be in line with the strategic planning that has been set. This research is expected to contribute to improving the performance of existing programs and activities in the Regional Government.